Factors associated with obesity in adult dogs from Lima, Peru - Segami C., Lia (2021)
The aim of this study was to determine the factors associated with the presentation of obesity in dogs treated at the Small Animal Clinic of the Faculty of Veterinary Medicine of the Universidad Nacional Mayor de San Marcos during 2017. In total, 89 dogs were included in the study. Sex, breed and body condition was recorded. Likewise, age, physical activity, neutering (yes/no) and type of diet were obtained through a survey applied to dog owners. The estimated body condition allowed the dogs to be classified between obese and non-obese. The average age was 7.7 years (0-16 years), with 50.6% (n=45) being female. Besides, 47.2% (n=42) were neutered and 28.1% (n=25) were crossbreds. Results showed that 46.1% (n=41) consumed balanced food as part of their diet and 74.2% (n=66) carried out regular physical activity. A total of 60.7% (n=54) were considered obese. Significant associations with the presentation of obesity were evidenced for a diet based on homemade food [OR 11.5; 95% CI: 2.96-44.65], purebreds compared to crossbreds [OR 4.34; 95% CI: 1.03-18.32] and age between 8 and 12 years compared to 1-year-old dogs [OR 20.13; 95% CI: 2.30-176.02]. No association was found with sex, physical activity and neutering.